Development Of Numbers Pyramid Media For Developing Cognitive Aspects Of Children Aged 5-6 Years - Rohyana Fitriani; Nopianti Nopianti; Zuhut Ramdani (Universitas Nusa Cendana, 2021)
The purpose of this research is to develop learning media in the form of a pyramid of numbers to develop the cognitive aspects of children aged 5-6 years. The development model used is Borg and Gall which consists of six stages. Products developed will be validated by a team of experts. The small scale subjects are 5 children and the large scale subjects are 15 children. The instrument used to collect data is an observation sheet. The results showed that the validation results of material experts obtained a score of 24 with an average value of 3.4 in the